Birch wood pre-hydrolysis vs pulp post-hydrolysis for the production of xylan-based compounds and cellulose for viscose application. (15th June 2018) - Borrega, Marc; Larsson, Per Tomas; Ahvenainen, Patrik; Ceccherini, Sara; Maloney, Thaddeus; Rautkari, Lauri; Sixta, Herbert
Highlights: Pulp post-hydrolysis results in higher cellulose yield than wood pre-hydrolysis. Elevated temperatures during post-hydrolysis promote supramolecular re-arrangements. Higher accessibility of OH groups in pre-hydrolyzed pulps. High purity and molar mass xylan extracted in high yield by water post-hydrolysis. Abstract: Hydrothermal treatments of birch wood and kraft pulp were compared for their ability to extract the xylan and produce viscose-grade pulp. Water post-hydrolysis of kraft pulp produced a high-purity cellulosic pulp with lower viscosity but higher cellulose yield than traditional pre-hydrolysis kraft pulping of wood. Post-hydrolysis of pulp also increased the crystallite dimensions and degree of crystallinity in cellulose, and promoted a higher extent of fibril aggregation. The lower specific surface area in post-hydrolyzed pulps, derived from their larger fibril aggregates, decreased the accessibility of OH groups. However, this lower accessibility did not seem to decrease the pulp reactivity to derivatizing chemicals. In the aqueous side-stream, the xylose yield was similar in both pre- and post-hydrolysates, although conducting post-hydrolysis of pulp in a flow-through system enabled the recovery of high purity and molar mass (∼10 kDa) xylan for high-value applications.